Educational Philosophy and Educational Practice in Confucianism - Xu, Yushu (2024)
Confucian educational thought is a complete educational theoretical system based on Confucius’ ethical thought, which is increasingly enriched and perfected in the later Confucian thinkers’ continuous inheritance and development. Confucian educational thought is different from Western educational theory. It takes moral education as the core, and ethics as the feature, with strong Chinese humanistic color. In modern education, the excellent educational thought of Confucianism is still talked about by people. From the perspective of philosophical analysis, this paper makes an in-depth study of the main purpose, content and method of Confucian educational thought, probes into the philosophical idea behind Confucian educational thought and summarizes its important enlightenment to contemporary education.